New organic-inorganic hybrid microporous organosilica having high metal ion adsorption capacity - Paul, Manidipa; Pal, Nabanita; Rajamohanan, P. R.; Rana, Bharat S.; Sinha, Anil K.; Bhaumik, Asim (Physical Chemistry Chemical Physics, 2010)
A new microporous organic-inorganic hybrid organosilica LHMM-2 containing a bis(propyliminomethyl)benzene moiety inside the framework has been synthesized hydrothermally without using any template or structure-directing agent. Powder XRD and TEM image analyses suggest a new disordered microporous structure with pores of dimension ca. 0.54 nm, and C-13 and Si-29 MAS NMR and spectroscopic results indicate the presence of bridging organic bis(propyliminomethyl) benzene moiety in this framework. TPD-NH3 results suggested that nearly 5 times as much bis(propyliminomethyl) benzene moiety is located inside the micropore walls (matrix) than in the surface of the pores. LHMM-2 shows very high adsorption capacity for metal cations like Fe3+, Cu2+ and Zn2+.

Effect of pt incorporation in LaBO3 (B = Mn, Fe, Co) perovskites on water gas shift activity - Rajesh, Thattarathody; Upadhyay, Anuj; Sinha, Anil K.; Deb, Sudip K.; Devi, R. Nandini (Journal of Molecular Catalysis A-Chemical, 2014)
Pt incorporated perovskites LaBO3 (B = Mn, Co, Fe) were synthesised and characterised to understand the charge state of Pt in these materials. At the temperature range used in this study, Pt could be stabilised in ionic form in Co and Fe perovskites but not in LaMnO3. Consequent to incorporation of Pt in +2 and +4 oxidation states, reduction in B site ion charge state occurred, enhancing oxygen vacancies. Pt doped Co and Fe perovskites showed high activity for CO conversion under water gas shift conditions but the activity characteristics were found to be different for the two catalysts; LaCo1-xPtxO3-delta showed methanation whereas the Fe counterpart was active in water gas shift reaction. It was also observed that methanation could be decreased and water gas shift enhanced in case of Pt doped Co perovskite when compared to Pt impregnated perovskite or mixed oxides. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Methanation; Perovskites; Pt doping; Water gas shift reaction; XANES

Mesoporous TUD-1 supported indium oxide nanoparticles for epoxidation of styrene using molecular O-2 - Rahman, Sumbul; Farooqui, Saleem A.; Rai, Aditya; Kumar, Rawesh; Santra, Chiranjit; Prabhakaran, Vinod C.; Bhadu, Gopala Ram; Sen, Debasis; Mazumder, S.; Maity, Sudip; Sinha, Anil K.; Chowdhury, Biswajit (RSC Advances, 2015)
Activation of molecular O-2 by metal or metal oxide nanoparticles is an area of recent research interest. In this work, for the first time, we report that indium oxide nanoparticles of <3 nm size dispersed on mesoporous silica (TUD-1) can activate molecular O-2 and produce styrene epoxide with a selectivity of 60% and styrene conversion around 25% under mild conditions. It is found that neither indium oxide nor TUD-1 themselves respond to the styrene epoxidation reaction. The computational studies provide evidence that an oxygen molecule is highly polarized when it is located near the interface of both surfaces. The kinetic study shows that the reaction is of pseudo-first order and that the activation energy for styrene conversion is 12.138 kJ mol(-1). The catalysts are recyclable for up to four regeneration steps, with the styrene conversion and styrene epoxide selectivity almost unchanged.